Studies on effect of coat thickness on the moisture uptake by a hardwood substrate - Sachin Gupta; Asieleavio John; V.S. Kishan Kumar (Maderas: Ciencia y Tecnología, 2016)
The moisture sorption behaviour of three coating thicknesses of shellac and polyurethane films on Dalbergia sissoo substrate is studied in this paper. The thin films of either coat failed to reduce the water vapour transmission significantly. However, the thick coats were able to reduce this rate illustrating the importance film thickness of coating used on surfaces of wood products. The increment in Moisture Content over the conditioned MC showed a clear film thickness effect in the case of PU with the increments reducing with increasing thickness. The Moisture Exclusion Effectiveness of PU coating showed better values than shellac coating with both the finishes showing a thickness effect. More importantly, the study illustrated the effect of coating thickness even when the differences are small.